Does short-time work save jobs? A business cycle analysis - Almut Balleer; Britta Gehrke; Wolfgang Lechthaler; Christian Merkl (Kiel Institute for the World Economy (IfW), 2013)
This paper analyzes the effects of short-time work (i.e., government subsidized working time reductions) on unemployment and output fluctuations. The central question is whether the rule based component (i.e., the existence of the institution short-time work) and the discretionary component (i.e., rule changes) stabilize employment over the business cycle. In our baseline scenario the rule based component stabilizes unemployment fluctuations by 15% and output fluctuations by 7%. Given the small share of short-time work expenses in terms of GDP, the stabilization effects are large compared to other instruments such as the income tax system. By contrast, discretionary short-time work interventions do not have any statistically significant effect on unemployment. These effects are based on a structural VAR estimation which is identified using the output elasticity of short-time work estimated from German establishment paneldata. The model shows that non-effects of discretionary interventions may be due to their low persistence.
Keywords: E24; E32; E62; J08; J63; 330; short-time work; fiscal policy; business cycles; search-and-matching; SVAR